2011
DOI: 10.1016/j.ejvs.2011.03.004
|View full text |Cite
|
Sign up to set email alerts
|

Aortorenal Bypass with Autologous Saphenous Vein in Takayasu Arteritis-induced Renal Artery Stenosis

Abstract: Our data suggest that ARB with autologous saphenous vein graft is safe, effective and durable in treating TARAS.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
19
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 28 publications
(28 reference statements)
3
19
0
Order By: Relevance
“…Overall, revascularization (both surgical and endovascular) was beneficial to BP control in the majority (53 %) of our patients. This positive effect of revascularization is in agreement with previous studies describing the benefits of revascularization procedures in terms of preservation of renal function and treatment of hypertension in adults and children with TA [5,8,11,12,21,[23][24][25][26][27][28][29][30]. Most previous studies on the outcome of renal revascularization on RVH in children originate from the Western world and report success rates of between 85 and 95 % [6][7][8][9][10]31].…”
Section: Discussionsupporting
confidence: 91%
“…Overall, revascularization (both surgical and endovascular) was beneficial to BP control in the majority (53 %) of our patients. This positive effect of revascularization is in agreement with previous studies describing the benefits of revascularization procedures in terms of preservation of renal function and treatment of hypertension in adults and children with TA [5,8,11,12,21,[23][24][25][26][27][28][29][30]. Most previous studies on the outcome of renal revascularization on RVH in children originate from the Western world and report success rates of between 85 and 95 % [6][7][8][9][10]31].…”
Section: Discussionsupporting
confidence: 91%
“…A primary patency of 75% was identified in the literature and used for aortorenal bypass patients who developed complications to determine whether this significantly influenced cost or value for aortorenal bypass compared to renal artery stenting, but none was found (Figure 2). 18,19 Similarly, a maximum five-year secondary patency of 87% was used for renal artery stent patients, but no significant difference in cost or value was found. 19 A composite endpoint of dialysis and death from all causes was used and as a basis of comparison to patients who were alive and dialysis-free at five years.…”
Section: Resultsmentioning
confidence: 99%
“…Five-year patency following aortorenal bypass is 95.0%, compared to 55.6% for renal artery stenting. 7,10,[18][19][20] The five-year patency was assumed to be similar between patients who had no complications and those who experienced one or more complications. A primary patency of 75% was identified in the literature and used for aortorenal bypass patients who developed complications to determine whether this significantly influenced cost or value for aortorenal bypass compared to renal artery stenting, but none was found (Figure 2).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Feng et al [5] reported the results of 33 patients treated by aortorenal bypass with autologous saphenous veins. In the 5-year follow-up, the patient's blood pressure lowered and anti-hypertensive medication dosage was reduced significantly.…”
Section: Discussionmentioning
confidence: 99%